Effects of the intranasal application of gold nanoparticles on the pulmonary tissue after acute exposure to industrial cigarette smoke. Issue 6 (11th December 2021) - Porto, Germano Duarte; Haupenthal, Daniela Pacheco dos Santos; Souza, Priscila Soares; Silveira, Gustavo de Bem; Nesi, Renata Tiscoski; Feuser, Paulo Emilio; Possato, Jonathann Corrêa; de Andrade, Vanessa Moraes; Pinho, Ricardo Aurino; Silveira, Paulo Cesar Lock
Abstract: Inhalation of harmful particles appears as a primary factor for the onset and establishment of chronic obstructive pulmonary disease (COPD). Cigarette smoke acutely promotes an exacerbated inflammatory response with oxidative stress induction with DNA damage. Administration of Gold Nanoparticles (GNPs) with 20 nm in different concentrations can revert damages caused by external aggravations. The effects of GNPs in a COPD process have not been observed until now. The objective of this work was to evaluate the therapeutic effects of intranasal administration of different doses of GNPs after acute exposure to industrial cigarette smoke. Thirty male Swiss mice were randomly divided into five groups: Sham; cigarette smoke (CS); CS + GNPs 2.5 mg/L; CS + GNPs 7.5 mg/L and CS + GNPs 22.5 mg/L. The animals were exposed to the commercial cigarette with filter in an acrylic inhalation chamber and treated with intranasal GNPs for five consecutive days. The results demonstrate that exposure to CS causes an increase in inflammatory cytokines, histological changes, oxidative and nitrosive damage in the lung, as well as increased damage to the DNA of liver cells, blood plasma and lung. Among the three doses of GNPs (2.5, 7.5, and 22.5 mg/L) used, the highest dose had better anti‐inflammatory effects. However, GNPs at a dose of 7.5 mg/L showed better efficacies in reducing ROS formation, alveolar diameter, and the number of inflammatory cells in histology, in addition to significantly reduced rate of DNA damage in lung cells without additional systemic genotoxicity already caused by cigarette smoke.